2018
DOI: 10.1017/s0954579418000962
|View full text |Cite
|
Sign up to set email alerts
|

Examining interactions between genetic risk for alcohol problems, peer deviance, and interpersonal traumatic events on trajectories of alcohol use disorder symptoms among African American college students

Abstract: Numerous studies have demonstrated that genetic and environmental factors interact to influence alcohol problems. Yet prior research has primarily focused on samples of European descent and little is known about gene-environment interactions in relation to alcohol problems in non-European populations. In this study, we examined whether and how genetic risk for alcohol problems and peer deviance and interpersonal traumatic events independently and interactively influence trajectories of alcohol use disorder sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
2
9
1
Order By: Relevance
“…This theoretically driven investigation tested peer environments modulating polygenic risks within a large prospective sample, controlling for key confounds (i.e., Sex × Friend Drinking; Parental Heavy Drinking × Friend Drinking) that ultimately explained adolescent drinking rather than G×E specifically. The current investigation replicates nonsignificant developmental G×E findings involving polygenic risks from two smaller samples (Li et al, 2017;Su et al, 2018), yet contradicts a recent twin study reporting stronger genetic risks in the presence of greater friend drinking from ages 13 to 17 (Zheng et al, 2019). Such discrepant findings may reflect generally larger heritability estimates among twin than polygenic risk studies (see Génin, 2020).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This theoretically driven investigation tested peer environments modulating polygenic risks within a large prospective sample, controlling for key confounds (i.e., Sex × Friend Drinking; Parental Heavy Drinking × Friend Drinking) that ultimately explained adolescent drinking rather than G×E specifically. The current investigation replicates nonsignificant developmental G×E findings involving polygenic risks from two smaller samples (Li et al, 2017;Su et al, 2018), yet contradicts a recent twin study reporting stronger genetic risks in the presence of greater friend drinking from ages 13 to 17 (Zheng et al, 2019). Such discrepant findings may reflect generally larger heritability estimates among twin than polygenic risk studies (see Génin, 2020).…”
Section: Discussioncontrasting
confidence: 55%
“…However, two additional investigations with polygenic risk scores of traitassociated variants yielded nonsignificant findings. Polygenic risk scores of alcohol dependence did not moderate associations of perceived friend substance use on heavy episodic drinking from adolescence into emerging adulthood (n = 412; Li et al, 2017) or associations of perceived friend de-viant behavior on alcohol use disorder symptom trajectories across college (n = 1,119; Su et al, 2018).…”
mentioning
confidence: 91%
“…Su, Kuo, Meyers, Guy, and Dick (2018) examined if polygenic risk for alcohol problems, peer deviance, and interpersonal trauma influenced trajectories of alcohol use disorder symptoms in a sample of 1,119 African American students across the college years. Polygenic risk did not predict trajectory of alcohol use.…”
Section: Investigating the Interplay Of Culture And Biology In Develomentioning
confidence: 99%
“…Evidence for the predictive utility of alcohol-related PGS has been mixed. One study found that a PGS for AUD was associated with levels of alcohol use in males at age 15.5 and greater increases of alcohol use at age 21.5 [16], while other studies predicting alcohol use in college student drinkers over time have returned both positive [17] and null results [18]. Most prior studies were limited by smaller GWAS discovery samples relative to the much larger recent GWAS consortia of alcohol and nicotine use.…”
Section: Introductionmentioning
confidence: 99%